Investment facilitation: Another fad in the offing? - Kavaljit Singh (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Discussions have begun in the WTO on investment facilitation. This Perspective questions the purpose of "top-down" multilateral binding rules on investment facilitation and suggests that the current proposals are far detached from ground realities.
Keywords: 330